Nanoparticle-Based Devices in the Control of Antibiotic Resistant Bacteria - Gómez-Núñez, Mario F.; Castillo-López, Mariel; Sevilla-Castillo, Fernando; Roque-Reyes, Oscar J.; Romero-Lechuga, Fernanda; Medina-Santos, Diana I.; Martínez-Daniel, Ricardo; Peón, Alberto N. (Frontiers in Microbiology, 2020)
Antimicrobial resistance (AR) is one of the most important public health challenges worldwide as it represents a serious complication that is able to increase the mortality, morbidity, disability, hospital stay and economic burden related to infectious diseases. As such, the spread of AR–pathogens must be considered as an emergency, and interdisciplinary approaches must be undertaken in order to develop not only drugs, but holistic strategies to undermine the epidemic and pathogenic potentials of multi-drug resistant (MDR) pathogens. One of such approaches has focused on the use of antimicrobial nanoparticles (ANPs), as they have demonstrated to possess strong antimicrobial effects on MDR pathogens. On the other hand, the ability of bacteria to develop resistance to such agents is minimal. In this way, ANPs may seem a good choice for the development of new drugs, but there is no certainty about their safety, which may delay its translation to the clinical setting. As MDR pathogens are quickly becoming more prevalent and drug development is slow and expensive, there is an increasing need for the rapid development of new strategies to control such agents. We hereby explore the possibility of designing ANP-based devices such as surgical masks and fabrics, wound dressings, catheters, prostheses, dentifrices, water filters, and nanoparticle-coated metals to exploit the potential of such materials in the combat of MDR pathogens, with a good potential for translation into the clinical setting.